How can we sustainably assess the shelf life of EVOO? A systematic review on analytical strategies and food waste reduction - Di Maria, Monica; Planeta, Diego; Venturini, Francesca; Torregrossa, Federica; Crupi, Pasquale (Frontiers in Nutrition, 2026)
Nowadays, olive oil quality is assessed through a combination of physicochemical parameters and sensory evaluation performed by trained tasting panels. The International Olive Council (IOC) and Codex Alimentarius define the legal limits and reference values for these parameters. The current analytical methods used to characterize extra virgin olive oil (EVOO), are based on destructive chemical techniques that are time-consuming, require long sample preparation (highly skilled operators), resource-intensive and involve the use of toxic solvents, with marked environmental impact and costs representing an obstacle in the green transition. Additionally, many of them do not allow for real-time analysis or analysis in line with industrial processes. Furthermore, none of the currently established methods adequately address the qualitative deterioration of virgin olive during storage. Thus, quality evaluation should include not only regulatory criteria but also parameters related to human health, the formation of degradation products, especially with respect to storage conditions. In addition, attention should be focused particularly on the concept of secondary shelf-life, with the aim of reducing food waste of olive oil while characteristics still remain unaltered. In light of this, it is necessary to explore alternative analytical strategies that are rapid, non-destructive, and sustainable, capable of guaranteeing the quality and safety of EVOO, reducing food waste, and respecting the principles of environmental sustainability. This review aims to critically analyze the latest analytical methodologies applied to determine the shelf life of EVOO, with a particular focus on their potential contribution to reducing waste and aligning with the objectives of Agenda 2030.